Effect of Net Profit Margin (NPM), Return On Assets (ROA) and Debt to Equity Ratio (DER) to Share Prices in Property Companies Registered on the Stock Exchange Indonesia (IDX) - Markonah Markonah; Yohanes Ferry Cahaya (Journal of Accounting and Finance Management, 2023)
Study This aim For know influence net profit margins (NPM), return on assets (ROA) and debt to equity ratio (DER) to prices shares in property companies listed on the Indonesia Stock Exchange (IDX). The population of this study consisted of property companies listed on the IDX on period 2017-2021. Determination of the research sample using the sampling method fed up. There are 35 property companies that meet the criteria. which method used is regression data panel with fixed effect. Results study shows that NPM has a significant negative effect to stock price on company property Which registered in IDX. ROA influential positive significant to the price of shares in property companies listed on the IDX Whereas DER No influential significant to price share on company property registered in IDX.